Composite material for power equipment, and cured composite material
Patent Information
- Application Number
- JP2023134781
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-03-07
AI Technical Summary
【0006】 本発明の一態様によれば、電力機器において高い絶縁性能を付与できる複合材料を提供できる。
Smart Images

Figure 2025029897000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to composite materials for electric power equipment and to cured composite materials. [Background technology]
[0002] Inorganic fillers having dielectric properties in which the dielectric constant increases with increasing electric field, and composite materials in which such inorganic fillers are dispersed in a polymer matrix are known (Patent Documents 1 and 2). By using the above composite materials in electric power equipment, the effect of mitigating the electric field in high electric field parts that may occur locally in the electric power equipment can be obtained. For example, when the above composite materials are used as a coating material for the inner wall of a sealed container (grounding tank) in a gas-insulated switchgear (GIS), electric field concentration near metal or other conductive foreign objects that may be present in the sealed container is mitigated. As a result, the decrease in partial discharge inception voltage is suppressed, which also prevents the floating of foreign objects, and suppresses the decrease in the insulation performance of the gas-insulated switchgear. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2007-182554 A [Patent Document 2] JP 2010-13642 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, insulating devices or insulating members in electric power equipment are required to have higher insulating performance. An object of the present disclosure is to provide a composite material capable of imparting high insulating performance to electric power equipment. [Means for solving the problem]
[0005] One aspect of the present invention is a composite material for electric devices, which contains a filler including a perovskite compound represented by ABO3 and a matrix including a low elastic modulus polymer. Effect of the Invention
[0006] According to one aspect of the present invention, a composite material capable of imparting high insulating performance to electric power equipment can be provided. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic diagram showing a configuration of a composite material for electric devices according to one embodiment. [Diagram 2] FIG. 2 is a diagram for explaining the crystal structure of an ABO3 type oxide. [Diagram 3] FIG. 1 is a cross-sectional view of a portion of a gas-insulated switchgear device having a coating layer including a composite material according to an embodiment. [Figure 4] 1 is a graph showing the results of an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] <Composite materials for electric power equipment and hardened composite materials> As shown in FIG. 1, one embodiment of the present invention is a composite material 1a for electric devices, which is formed by dispersing a predetermined filler 2 in a base material (matrix) 3 containing a predetermined polymer. Another embodiment is a cured composite material which is a cured product formed by curing the composite material 1a. In the cured composite material, the filler is also dispersed in a cured product of a base material containing a predetermined polymer (hereinafter, also referred to as a polymer base material cured product or a base material cured product). The composite material 1a for electric devices (FIG. 1) may contain components such as a curing agent and a curing accelerator depending on the type of the curing agent.
[0009] The filler used in this embodiment is a material having a dielectric property in which the dielectric constant increases with an increase in the electric field (hereinafter, also referred to as the electric field dependence of the dielectric constant), and may contain a perovskite compound represented by ABO3 (described later). By using such a material having an electric field dependence of the dielectric constant as, for example, a coating material (described later) for a member of an electric power device or a molding material for the member, an effect of mitigating a high electric field that may occur locally in the electric power device (hereinafter, also referred to as the electric field mitigation effect) can be obtained. This effect suppresses a decrease in the partial discharge inception voltage and prevents insulation breakdown, etc., so that the reliability of the electric power device used under a high electric field can be improved.
[0010] Examples of electric power equipment include gas-insulated switchgear (GIS), transformers (including molded transformers, etc.), switchboards, semiconductor devices, etc. The composite material according to one embodiment can be used as a coating material for coating the surfaces of insulating members and / or conductive members of such electric power equipment, particularly those to which high voltage is applied, or as a molding material for insulating members.
[0011] The composite material is particularly suitable for use as a coating material (described later in detail) formed on the inner surface of a sealed container (ground tank) of a gas-insulated switchgear (GIS). For example, the inner wall surface of the sealed container of a gas-insulated switchgear (GIS) may contain conductive foreign matter such as metals that are mixed in or generated during the manufacturing process or use of the device. Since an electric field is likely to concentrate near such foreign matter, partial discharge is likely to occur and insulation breakdown is likely to occur. In particular, if a charged foreign matter floats from the inner wall and approaches or adheres to the central conductor, this may cause a further decrease in the partial discharge inception voltage and may cause a correlation short circuit or a ground fault. In contrast, by using a composite material containing a filler having a dielectric constant that is dependent on the electric field and a polymer as a coating material provided on the inner wall of the sealed container, the electric field concentrated near the foreign matter is also shared by the filler having a dielectric constant that is dependent on the electric field near the foreign matter, so that charging of the foreign matter and thus floating of the foreign matter can be prevented, and a decrease in the partial discharge inception voltage can be suppressed.
[0012] The demand for suppressing partial discharge in insulating devices or insulating members of electric power equipment is becoming increasingly strict, and in order to meet this demand, a composite material capable of imparting higher insulating performance is required. The present inventors have found that using a polymer (described in detail later) having a predetermined elastic modulus characteristic as the main component polymer of the base material of the composite material contributes to suppressing the decrease in partial discharge inception voltage and thus improving insulating performance. The polymer having the predetermined elastic modulus characteristic may be a low elastic modulus polymer, i.e., a polymer that exhibits a low elastic modulus in the cured state.
[0013] When a local high electric field occurs, the dielectric constant of the filler in the vicinity immediately below the high electric field portion increases, but this increase in dielectric constant is caused by the displacement of ions in the crystals of the filler. At this time, the displacement of ions in the filler directly affected by the high electric field causes the hardened polymer matrix around the filler to deform, and it is considered that the deformation of the hardened polymer matrix also causes the displacement of ions in the crystals of the filler away from the position where the high electric field occurs. As a result, the increase in the dielectric constant of the filler occurs not only near the position where the high electric field occurs but also over a relatively wide range, and it is considered that such an increase in the dielectric constant of the entire composite material over a relatively wide range may reduce the partial discharge inception voltage and ultimately lead to a decrease in insulation performance. In contrast, in this embodiment, by using a low modulus polymer, i.e., a polymer that shows a low modulus of elasticity in a cured state, as the main component of the matrix, even if the displacement of ions occurs in the filler due to a local high electric field, the deformation of the hardened polymer matrix caused by the displacement is limited to a very small range around the filler displaced by the high electric field. For this reason, it is believed that the range in which the dielectric constant increases in the composite material can be made very small, and the partial discharge inception voltage can be maintained high.
[0014] In this manner, by using a polymer that exhibits a low modulus of elasticity in a cured state as the main component of the base material, the present embodiment provides a higher insulating performance than a composite material using a conventional polymer, even if the same type of filler is mixed at the same content. The composite material that provides such high insulating performance can be an alternative to insulating gases that have been used as excellent insulating means in electric power equipment. That is, by using the composite material according to the present embodiment, the use of insulating gases can be eliminated or reduced. SF6 gas is known as an example of an insulating gas with high insulating properties, but SF6 gas is also known as a greenhouse gas, so the present embodiment, which can be used as an alternative to SF6 gas, is also preferable from the viewpoint of environmental conservation.
[0015] <Filling material> As described above, the filler used in the composite material for electric devices according to one embodiment may be a filler having a dielectric property (dielectric constant electric field dependence) in which the dielectric constant increases with an increase in the electric field. Such a filler may be a ferroelectric or antiferroelectric. More specifically, the filler may be a perovskite-type compound represented by the general formula ABO3 (hereinafter, also referred to as ABO3-type oxide). In the general formula ABO3, A is an element constituting an m-valent cation (A site ion), B is an element constituting an n-valent cation (B site ion), and m+n=6. In the general formula ABO3, A may be one type, or two or more types, for example, two or three types, and B may be one type, or two or more types, for example, two or three types. An ABO3-type oxide in which A and / or B are two or more types can be said to be an ion-doped oxide.
[0016] Figure 2 shows a schematic of the crystal structure of a perovskite compound represented by ABO3. As shown in Figure 2, ABO3 oxides have a structure in which the vertices of a cubic crystal are the A sites, the B sites are at the body centers of the cube, and oxygen atoms are at the face centers. The ionic radius of the A site ions is larger than that of the B site ions.
[0017] Furthermore, it is preferable that the ABO3 type oxidant has a certain tolerance factor t. The tolerance factor t is represented by the following formula (1): t=(r a +r o ) / {√2(r b +r o )}···(1) In formula (1), r a is the cation radius of the A site, r b is the cation radius of the B site, r o is the radius of the anionic oxygen.
[0018] In addition, the A site has a cation radius r a1 A 1 , and the cation radius r a2 A 2 It consists of two different types, A 1 The mole fraction of x1, A 2 When the mole fraction of is x2, the tolerance factor t is expressed by the following formula (2): t={(r a1 x1+r a2 x2)+r o} / {√2(r b +r o )}···(2)
[0019] The tolerance factor t of the ABO3 type oxide may be preferably 0.8 or more and 1.1 or less. When the tolerance factor t is in the above range, the ABO3 type oxide exhibits a relatively large electric field dependence of the dielectric constant, and therefore an excellent electric field relaxation effect can be obtained. When the tolerance factor t is more than 1, it is preferable from the viewpoint of forming a ferroelectric material with a larger electric field dependence.
[0020] In the general formula ABO3, A may be, for example, one or more selected from the group consisting of Ba, Pb, Sr, K, Na, and Ca, and B may be, for example, one or more selected from the group consisting of Zr, Nb, and Ti. Specific examples of ABO3 type oxides include BaTiO3, PbTiO3, SrTiO3, KNbO3, BaZrO3, KTaO3, CaZrO3, PbZrO3, CaTiO3, SrSnO3, SrZrO3, and NaNbO3. These ABO3 type oxides can be used alone or in combination of two or more. Among these, one or more selected from the group consisting of BaTiO3, SrZrO3, and CaZrO3 are preferred, since they have a high dielectric constant electric field dependency and are excellent in the effect of alleviating electric field concentration, and BaTiO3 is more preferred.
[0021] In addition, if the obtained composite material has a dielectric constant dependent on the electric field, exhibits a high dielectric constant under a high electric field, and has the effect of alleviating an electric field that may occur locally in an electric device, the filler may contain an inorganic filler other than the ABO3 type oxide. The inorganic filler other than the ABO3 type oxide may be SiC, Al2O3, SiO2, etc. However, from the viewpoint of improving the electric field relaxation effect, it is preferable that the filler contains 80 volume % or more, 90 volume % or more, or 95 volume % or more of the ABO3 type oxide with respect to the total amount of the filler, and it is preferable that the filler is substantially composed of the ABO3 type oxide. In this specification, when it is said that a certain object is substantially composed of a specified component, it means that components such as impurities other than the specified component may be included due to the raw material or unavoidably during production.
[0022] The filler may be in the form of particles or powder. The average particle size of the filler may be preferably 0.1 μm to 200 μm, more preferably 0.5 μm to 50 μm. When the filler has an average particle size in the above range, the filler can be more uniformly dispersed in the base material, and the filler becomes easier to handle during the production of a composite material. In this specification, the average particle size is a volume-based diffusion coefficient equivalent diameter measured by a laser diffraction / scattering method.
[0023] The content of the filler may be preferably 1% by volume or more and 50% by volume or less, more preferably 5% by volume or more and 20% by volume or less, based on the total amount of the composite material, i.e., 100% by volume of the composite material. By making the content of the filler 1% by volume or more, the electric field dependency of the dielectric constant of the filler is fully exhibited, and the effect of relaxing the locally generated electric field can be further improved, thereby contributing to the improvement of the insulating performance. On the other hand, by making the content of the filler 50% by volume or less, the increase in the relative dielectric constant of the entire composite material is suppressed, and the decrease in the partial discharge inception voltage is suppressed, thereby improving the insulating performance. In addition, by reducing the proportion of the polymer constituting the composite material, it is possible to prevent the insulating performance inherent to the polymer from being impaired, and the properties inherent to the polymer, such as toughness, flexibility, and ease of processing, from being impaired, which leads to a decrease in handleability and processability.
[0024] <Base material and polymer> The matrix in the composite material according to one embodiment mainly contains a polymer. In this specification, "mainly containing a polymer" may mean that the content of the polymer relative to the total amount of the matrix is 80% by volume or more, 90% by volume or more, or 95% by volume or more. It is also preferable that the matrix is substantially composed of a polymer.
[0025] The polymer used in this embodiment is not particularly limited in type, but as described above, has a predetermined elastic modulus characteristic. The polymer having the predetermined elastic modulus characteristic is a polymer that, even if the hardened product of the polymer is subjected to an external force or stress generated inside, easily deforms in response to the external force or stress and has flexibility capable of absorbing the external force or stress within a microvolume. More specifically, in the hardened product of the polymer matrix, when there is a displacement of an ion in the crystal of the filler, only the microvolume in the vicinity of the displaced ion is easily deformed, and the stress generated in the hardened product of the polymer matrix is also absorbed within the microvolume. Such a predetermined elastic modulus characteristic of the polymer can be evaluated by measuring the elastic modulus of the polymer after curing. The polymer in this embodiment has a low elastic modulus of a predetermined value or less in the hardened state. The elastic modulus characteristic of the polymer can also be evaluated by another method, such as a nanoindentation test (a test in which an indenter is pressed into a polymer and the elastic modulus is measured by calculation from the load-displacement curve obtained).
[0026] Here, the elastic modulus measured for evaluating the above-mentioned properties may be one or more of storage modulus, loss modulus, tensile modulus, shear modulus, and bulk modulus. Among these, the polymer used in the present embodiment may preferably be a polymer exhibiting a low storage modulus.
[0027] The storage modulus of the polymer in the cured state may be preferably 10 MPa or more and 1000 MPa or less, more preferably 50 MPa or more and 500 MPa or less, and even more preferably 50 MPa or more and 200 MPa or less at 25 ° C. When the storage modulus is 10 MPa or more, the function as the matrix cured product in the composite material can be ensured, and appropriate shape retention can be obtained. In addition, when the storage modulus is 1000 MPa or less, the above-mentioned elastic modulus characteristics are fully expressed. That is, when the displacement of ions in the crystal of the filler occurs, the range of the polymer matrix that is deformed under the influence of the displacement can be kept small, and the range in which the relative dielectric constant of the composite material increases can be kept small, and the deterioration of the insulating performance can be prevented.
[0028] The polymer used in this embodiment may be any of thermoplastic polymers, thermosetting polymers, and combinations thereof, as long as it has the above-mentioned predetermined elastic modulus characteristics, and may be preferably a thermosetting polymer. The polymer may be one or more of resin, rubber, and elastomer. Specific examples of the polymer include epoxy resin, polyurethane resin, silicone resin, ethylene-propylene copolymer (EPM), ethylene-propylene-diene copolymer (EPDM), etc., among which epoxy resin is preferred because the polymer itself has high electrical insulation and high mechanical strength. The above polymers may be used alone or in combination of two or more. The polymer may be a homopolymer or a copolymer. The polymer may be a polymer blend in which two or more different polymers are blended.
[0029] The polymer is cured in the cured composite material to form a cured polymer. The polymer can be cured with or without the use of a curing agent and / or a curing accelerator (curing assistant). Therefore, the cured composite material for electric equipment may contain a curing agent and / or a curing accelerator.
[0030] When the polymer is an epoxy resin, it may have two or more reactive groups per molecule, and is preferably an epoxy resin having reactive groups at least at both ends. The reactive groups are, for example, epoxy groups, and when the polymer is cured, a crosslinked structure is formed via the reactive groups to obtain a cured product.
[0031] The epoxy resin may include a soft segment (flexible backbone) and a hard segment (rigid backbone). The soft segment may be a segment derived from one or more of aliphatic polyethers and aliphatic polyesters, and may preferably be a segment derived from aliphatic polyethers. Specific examples include a segment derived from polyethylene glycol (a group having an oxyethylene group as a repeating unit) and a polypropylene glycol (a group having an oxypropylene group as a repeating unit). The hard segment may be a segment derived from one or more of saturated alicyclic hydrocarbons, unsaturated alicyclic hydrocarbons, and aromatic hydrocarbons, and may preferably be a segment derived from aromatic hydrocarbons. Specific examples of the hard segment include a segment derived from bisphenol A and a segment derived from bisphenol F. Furthermore, it is preferable that the soft segment and the hard segment are bonded via a divalent group derived from acetal. Therefore, the divalent group derived from acetal may be an alkyl alkylene group, and examples thereof include a methyl methylene group, a methyl ethylene group, a propylene group, and a trimethylene group. By using such an epoxy resin having a structural unit in which a soft segment and a hard segment are bonded via an acetal-derived divalent group, the polymer can have the above-mentioned specified elastic modulus characteristics, i.e., the polymer can exhibit a low elastic modulus in a cured state.
[0032] When the polymer is an epoxy resin and a curing agent is used to cure the polymer, the curing agent may be one or more of an acid anhydride curing agent and an amine curing agent. Examples of the acid anhydride curing agent include phthalic anhydride, methyl hymic anhydride, hexahydrophthalic anhydride, methyl tetrahydrophthalic anhydride, methyl hexahydriphthalic anhydride, and the like. Examples of the amine curing agent include diethylene triamine, triethylene tatramine, tetraethylene pentamine, meta xylene diamine, and the like. In the composite material for electric power equipment, the amount of the curing agent contained in the base material may be 90 to 110 mol parts per 100 mol parts of epoxy resin, and may preferably be equivalent to the epoxy resin (an amount in which the epoxy equivalent of the epoxy resin is equal to the equivalent of the reactive group of the curing agent). Furthermore, when the curing agent is an acid anhydride, N,N-dimethylbenzylamine, etc. can be used as a curing accelerator.
[0033] When the polymer contains a polyurethane resin, it has a structure including a segment derived from a polyol compound and a segment derived from a polyisocyanate compound. Examples of the polyol compound include polyether polyol, polyester polyol, polybutadiene polyol, polyisoprene polyol, etc. Examples of the polyisocyanate compound include aliphatic polyisocyanate compounds, alicyclic polyisocyanate compounds, aromatic polyisocyanate compounds, and aromatic aliphatic polyisocyanate compounds.
[0034] When the polymer comprises a silicone resin, the silicone resin may be a curable silicone resin having an organopolysiloxane skeleton represented by the following formula: (CH3) a Si(OR 1 ) b (OH) c O (4-a-b-c) / 2 In the formula, R 1each independently represents an organic group having 1 to 4 carbon atoms, and a, b, and c are numbers that satisfy 0.8≦a≦1.5, 0≦b≦0.3, 0.001≦c≦0.5, and 0.801≦a+b+c<2. The weight average molecular weight of the silicone resin in terms of polystyrene may be 1,000 to 20,000.
[0035] When the polymer contains a silicone resin and curing is used to cure the polymer, a curing accelerator may be used, such as an organic zinc acid such as zinc benzoate, an organic aluminum compound such as aluminum acetylacetonate, or an organic titanium compound such as tetrabutyl titanate.
[0036] When the polymer includes ethylene-propylene-diene copolymer (EPDM), examples of the polymer may include a terpolymer of ethylene, propylene, and one or more non-conjugated diene components such as 1,4-hexadiene, hexacyclodiene, and 5-ethylidene-2-norbornene. When the polymer includes one or more of ethylene-propylene copolymer (EPM) and ethylene-propylene-diene copolymer (EPDM), an organic oxide such as dicumyl peroxide can be used as a curing accelerator.
[0037] In the composite material for electric equipment, the content of the base material may be 50% by volume or more and 99% by volume or less, more preferably 80% by volume or more and 95% by volume or less, based on the total amount of the composite material, i.e., 100% by volume of the composite material. By making the content of the base material 50% by volume or more, the filler is appropriately dispersed, which improves the effect of suppressing the increase in the relative dielectric constant of the entire composite material obtained, suppresses the decrease in the partial discharge inception voltage, and improves the insulating performance. In addition, the toughness, flexibility, ease of processing, etc. of the obtained composite material are also ensured, and the handling and processability are improved. On the other hand, by making the content 99% by volume or less, the insulating performance can be improved without hindering the electric field relaxation effect of the filler.
[0038] The polymer contained in the matrix may contain a polymer other than the low modulus polymer (non-low modulus polymer) as long as the function of the low modulus polymer is not impaired. However, the content of the low modulus polymer is preferably 60% by volume or more and 100% by volume or less with respect to the total amount of polymer contained in the matrix.
[0039] The content of the low modulus polymer may be preferably 70% by volume or more and 99% by volume or less, more preferably 80% by volume or more and 95% by volume or less, based on the total amount of the composite material. By making the content 70% by volume or more, the above-mentioned effect of suppressing the increase in the overall relative dielectric constant in the obtained composite material can be improved, the decrease in the partial discharge inception voltage can be suppressed, and the insulating performance can be improved. In addition, the toughness, flexibility, etc. of the low modulus polymer can be imparted to the obtained composite material. On the other hand, by making the content 99% by volume or less, the insulating performance can be improved without impeding the electric field relaxation effect of the filler.
[0040] In addition, components other than the polymer in the base material include the above-mentioned curing agent and curing accelerator, as well as other additives. Examples of the other additives include colorants, anti-settling agents, and defoamers.
[0041] <Coating materials for power equipment> As described above, the composite material for electric power equipment is suitably used as a coating material for electric power equipment. The coating material for electric power equipment is a coating material for coating the surface of a member in an electric power equipment, particularly an insulating member and / or a conductive member. When the composite material is used as a coating material, the composite material (pre-cured material) is coated on a member for an electric power equipment by painting or the like, and then cured by heating or leaving to stand, so that a layer made of the cured composite material can be formed on the member.
[0042] FIG. 3 shows an example in which the cured composite material according to this embodiment is used as a coating material in a sealed container (ground tank) 13 of a gas insulated switchgear (GIS). FIG. 3 is a cross-sectional view taken along the axis of the central conductor 11 of the sealed container 13. The central conductor 11 to which a high voltage is applied is housed in the sealed container 13, and a cone-shaped insulating spacer 12 is provided to support the central conductor 11. A gas 14 is sealed in the space within the sealed container 13. The central conductor 11 is made of aluminum, the insulating spacer 12 is made of a resin insulator containing a filler, and the inner wall surface of the sealed container 13 may be made of aluminum or iron. The gas 14 may be one or more of air, SF6 gas, and an SF6 substitute gas.
[0043] The cured composite material 1 is formed as a coating layer on a part or all of the inner surface of the sealed container 13 (the surface exposed to the space inside the sealed container), more specifically, the inner wall surface of the sealed container, the surface of the insulating spacer, and the surface of the central conductor. It is preferable that the coating layer made of the cured composite material 1 is formed at least on the surface of the insulating spacer.
[0044] When the composite material for electric equipment is used as a coating material for the surface of electric equipment, the thickness of the coating material layer before curing may be preferably 1 μm or more and 100 μm or less, more preferably 30 μm or more and 100 μm or less. When the composite material for electric equipment is used as a coating material, from the viewpoint of ease of application, the viscosity of the coating material is preferably 1 Pa s or more and 20 Pa s or less. EXAMPLES
[0045] The present invention will be described in further detail below with reference to examples.
[0046] <Sample preparation> Example 1 100g of epoxy resin E1 (DIC Corporation, EXA4850-150) and 63g of filler BaTiO3 (Nippon Chemical Industry, Parceram BT-UP2, spherical particles, average particle size: 2μm) were kneaded using a planetary centrifugal mixer, and 5.4g of triethylenetetramine (Tokyo Chemical Industry) (equivalent to epoxy resin E1) was added and further kneaded to obtain a composite material, which was then cast into a plate shape. The mixture was cured at room temperature (25°C) for 24 hours to obtain a plate-shaped sample (cured product) of 150mm x 150mm x 0.26mm. The epoxy resin E1 is a resin containing a structural unit in which a soft segment derived from polyethylene glycol and a hard segment derived from bisphenol A are bonded via a methylmethylene group. The content of the filler BaTiO3 was 10% by volume relative to the total amount of the composite material.
[0047] Example 2 A plate-shaped sample was prepared in the same manner as in Example 1, except that the content of BaTiO3 was 30 volume % with respect to the total volume of the composite material.
[0048] Example 3 A plate-shaped sample was prepared in the same manner as in Example 1, except that the content of BaTiO3 was 35 volume % with respect to the total volume of the composite material.
[0049] Comparative Example 1 A plate-shaped sample was prepared in the same manner as in Example 1, except that BaTiO3 was not added.
[0050] Comparative Example 2 100 g of epoxy resin e1 (Mitsubishi Chemical, JER828, epoxy resin for casting) and 63 g of filler BaTiO3 (Nippon Chemical Industry, Parceram BT-UP2, spherical particles, average particle size: 2 μm) were kneaded using a planetary centrifugal mixer, and 12.8 g of triethylenetetramine (equivalent to epoxy resin e1) was added and further kneaded to obtain a composite material, which was then cast into a plate shape. After that, the mixture was degassed and heat-cured in the same manner as in Example 1 to obtain a plate-shaped sample of the same size. The content of the filler BaTiO3 was 10% by volume relative to the total amount of the composite material (material before heating).
[0051] Comparative Example 3 A plate-shaped sample was prepared in the same manner as in Comparative Example 2, except that the content of BaTiO3 was 35 volume % with respect to the total volume of the composite material.
[0052] <Measurement and evaluation of sample characteristics> (Polymer properties) The storage modulus was measured as a polymer characteristic. Specifically, in each example, a sample was prepared separately without blending a filler, and the storage modulus of the sample was measured using a dynamic viscoelasticity measuring device (DMS6100, manufactured by Hitachi High-Tech Science Corporation) under the conditions of a measurement temperature of 25°C, a measurement mode of tension, a strain amplitude of 10 μm, a measurement frequency of 1 Hz, and a temperature rise rate of 10°C / min. The storage modulus of epoxy resin E1 (used in Examples 1 to 3) was 100 MPa, and the storage modulus of epoxy resin e1 (used in Comparative Examples 2 and 3) was 2500 MPa.
[0053] (Dielectric constant of sample) The relative dielectric constant of the plate-shaped sample obtained in each example was measured by a method conforming to JIS C2138: 2007. The measured dielectric constant was a value at an applied voltage of 5 V and a measurement frequency of 1 kHz.
[0054] <Evaluation of electric field relaxation characteristics> The electric field relaxation characteristics of the plate-shaped specimens obtained in each example were evaluated using parallel plate electrodes as follows. Specifically, a conductive paint (Dotite D-500, manufactured by Fujikura Kasei Co., Ltd.) was applied to one side of the plate-shaped specimen, and the plate-shaped specimen was placed so that the side on which the paint was applied was in contact with the earth electrode side of the parallel plate electrodes. A metal thin wire (φ0.2 mm×5 mm, made of Cu) was placed as a metal foreign body in the approximate center of the surface of the plate-shaped specimen facing the high-voltage electrode, and was fixed with Kapton adhesive tape (manufactured by Toray DuPont Co., Ltd.). Then, a high AC voltage was applied to the parallel plate electrodes at a voltage rise rate of 200 V / s and a commercial frequency (50 Hz), and the partial discharge inception voltage was measured. For the measurement, a tuned partial discharge meter (CD-5, manufactured by Nippon Keisokuki Co., Ltd.) was used, and the time when a discharge charge of 1 pC occurred was defined as the time when partial discharge occurred, and the voltage at that time was defined as the partial discharge inception voltage. When partial discharge voltage occurred, the application of voltage was stopped, and the plate sample was neutralized with a neutralizing rod. The measurement was then repeated 10 times to calculate the average value.
[0055] The measurement results are shown in FIG. 4. As shown in FIG. 4, even if the same filler is filled at the same ratio, the example using resin E1 with a low elastic modulus has a higher partial discharge inception voltage and improved insulation performance compared to the example using resin e1 with a higher elastic modulus (comparison between Example 1 and Comparative Example 2, and comparison between Example 3 and Example 3). Furthermore, it was also found that the partial discharge inception voltage cannot be increased as the filler content ratio increases. It was found that the example (Example 1) with a filler content ratio of 10 volume % had a higher partial discharge inception voltage and better insulation performance compared to the examples (Examples 2 and 3) with a higher filler content ratio than that example. This is thought to be because the increase in the relative dielectric constant of the entire composite material due to the increase in the filler content affects the insulation performance.
[0056] Although the present invention has been described above based on the embodiments and examples, the present invention is not limited to these embodiments. Furthermore, the above embodiments can be changed, modified, substituted, added, deleted, and combined in various ways within the scope of the claims, and these also belong to the technical scope of the present invention. [Explanation of symbols]
[0057] 1 Cured composite material 1a Composite materials 2 Filling material 3. Polymer matrix 11 Center conductor 12 Insulating spacer 13 Sealed container (grounded tank) 14 Insulating gas
Claims
1. A.B.O. 3 A filler containing a perovskite type compound represented by the formula: A composite material for electric power equipment, comprising: a matrix containing a low elastic modulus polymer.
2. 2. The composite material for electric instruments according to claim 1, wherein the low elastic modulus polymer has a storage modulus in a cured state of 10 MPa or more and 1,000 MPa or less.
3. 3. The composite material for electric equipment according to claim 1 or 2, wherein the low modulus polymer comprises one or more selected from the group consisting of an epoxy resin, a polyurethane resin, a silicone resin, an ethylene-propylene copolymer (EPM), and an ethylene-propylene-diene copolymer (EPDM).
4. the low modulus polymer comprises an epoxy resin; 4. The composite material for electric equipment according to claim 3, wherein the epoxy resin contains a structural unit in which a soft segment derived from an aliphatic polyether and a hard segment derived from bisphenol A are bonded via a divalent group derived from an acetal.
5. The filler is BaTiO 3 , SrZrO 3 , and CaZrO 3 The composite material for electric equipment according to claim 1 or 2, comprising one or more selected from the group consisting of:
6. 3. The composite material for electric devices according to claim 1, wherein a content of the filler is 1 volume % or more and 50 volume % or less with respect to a total amount of the composite material for electric devices.
7. The composite material for electric equipment according to claim 1 or 2, which is a coating material for electric equipment.
8. A cured composite material which is a cured product of the composite material for electric equipment according to claim 1 or 2.
Citation Information
Patent Citations
Antiferroelectric polymer composite, method of manufacture thereof, and article comprising the same
JP2007182554A
High temperature polymer composite and method of producing the same
JP2010013642A